If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3.5 = 6.4x + -16.42 Reorder the terms: -3.5 + 3x = 6.4x + -16.42 Reorder the terms: -3.5 + 3x = -16.42 + 6.4x Solving -3.5 + 3x = -16.42 + 6.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.4x' to each side of the equation. -3.5 + 3x + -6.4x = -16.42 + 6.4x + -6.4x Combine like terms: 3x + -6.4x = -3.4x -3.5 + -3.4x = -16.42 + 6.4x + -6.4x Combine like terms: 6.4x + -6.4x = 0.0 -3.5 + -3.4x = -16.42 + 0.0 -3.5 + -3.4x = -16.42 Add '3.5' to each side of the equation. -3.5 + 3.5 + -3.4x = -16.42 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + -3.4x = -16.42 + 3.5 -3.4x = -16.42 + 3.5 Combine like terms: -16.42 + 3.5 = -12.92 -3.4x = -12.92 Divide each side by '-3.4'. x = 3.8 Simplifying x = 3.8
| 2t+7t=45 | | 7.79=2(3.14*r) | | (8-5i)(8-5i)= | | -(5y+5)-(-4y-6)=-3 | | 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 | | -4(2b+3)+(9b-7)=0 | | 5(4x-6)-19x=7 | | 4x+1=2(x-7) | | b+8b-22=0 | | 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 | | 5x/6-y/3=6 | | 19m=40-17.95 | | 36m^2-49/16=0 | | 37=-2(22-X)+3(X-3) | | (9-3x)(9-5x)= | | -11x^2+3x+11=0 |